Southern African economic integration: evidence from an augmented gravity model - Thierry Warin; Phanindra V. Wunnava; Optat Tengia; Kirsten Wandschneider (Institute for the Study of Labor (IZA), 2009)
This paper investigates the feasibility of creating a common-currency union consisting of 16 countries in Southern Africa. We estimate an augmented-gravity model that includes public deficit, public debt, public expenditure, inflation, and the foreign reserves position. We also integrate Africa-specific variables such as existing economic blocs in the region, colonial heritage, and the convergence of living standards. Our analysis shows that the prospect for further integration in Southern Africa is promising, but many challenges still persist. The existing economic blocs can provide a first stepping stone to a larger currency union, but countries continuously have to cultivate good governance and fiscal discipline.
urn:nbn:de:101:1-20090825553
Keywords: F1; F3; F4; O24; O55; 330; Optimum currency area; gravity model; Southern African integration; endogenous optimum currency area theory; Währungsunion; Optimaler Währungsraum; Gravitationsmodell; Wirtschaftsintegration; Südliches Afrika; SADC-Staaten